THE EFFECTS OF AGE ON BIOCHEMISTRY PROFILES OF ACEH CATTLE BLOOD - Lia Khairita; Anita Esfandiari; Sus Derthi Widhyari; Wiwin Winarsih (Jurnal Kedokteran Hewan, 2021)
The purpose of this study was to analyze the effects of age on the biochemistry profiles of aceh cattle, which  included examinations of: total protein (TP), albumin, globulin, albumin/globulin ratio (A/G), aspartate aminotransferase (AST), gamma-glutamyltransferase (GGT), alkaline phosphatase (ALP), creatine kinase (CK), blood urea nitrogen (BUN), calcium (Ca), phosphorus (P) and magnesium (Mg) . Sixteen clinically healthy aceh cattle aged 2-4 years old, and 16 aceh cattle aged 4-6 years old were purposively selected for the study. Blood samples were drawn from the jugular vein and subjected to blood biochemistry measurements using commercial kits. The results showed that serum concentrations of TP, globulin, AST and Ca of aceh cattle were significantly (P0.05) higher in age group 4-6 years old, while ALP activity was significantly (P0.05) higher in age group 2-4 years old. In conclusion, age must be considered as a factor when interpreting the blood biochemistry profiles of aceh cattle.